UMP e-saman system using mobile - Raiha Nadia, Mohd Ariffin (2019)
UMP E-Saman System Using Mobile is mobile application system where it handles summon in the Universiti Malaysia Pahang (UMP). The user of this system will be UMP Security Officer. They will use this system to issuing the summons on staff and students that do traffic offence. This system will scan a QR code on the UMP vehicle sticker. The QR code itself will have data which is student name/staff name, matric number/Staff ID and car plate. For those who do not have vehicle sticker, the system will provide the user to key in the car plate and type of traffic offence. Hence, all the data will insert into a database system. Since the mobile technology is growing further. I think this application system will give a benefit towards the user which is UMP Security Officer. I hope this application can be used with satisfied as it is very convenience and suitable for upcoming generations.